Effects of city wastewater on the characteristics of wheat with varying doses of nitrogen, phosphorus, and potassium - Akhtar, Neelima; Inam, Arif; Inam, Akhtar; Khan, Nafees A (Recent Research in Science and Technology, 2012)
Rapidly growing India is not only facing the problem of water scarcity, but also the mismanagement of tremendous amount of wastewater produced every day. Moreover, food sufficiency has also become challenge to feed the ever increasing population leading to excessive use of chemical fertilizers in agriculture. Therefore, the study was carried out in Aligarh City of India on wheat crop (Triticum aestivum L.) var. PBW 343 to check the suitability of city wastewater as a source of irrigation water as well as source of nutrients. Three pot experiments were conducted in the winter season of 2006-2008. In Experiment I, nitrogen (N) at the rate of 0, 40, 80, 120 kg ha-1; Experiment II, phosphorus (P) at the rate of 0, 20, 40, 60 kg ha-1; and in Experiment III, potassium (K) at the rate of 0, 15, 30 and 45 kg ha-1 were applied along with the basal doses under the three levels of water; ground water (GW), 50% wastewater (WW) and 100% WW. Lower fertilizer doses, 80 kg N ha-1, 40 kg P ha-1 and 30 kg K ha-1 together with 100%WW proved optimum in three experiments, respectively, enhancing tiller number plant-1, fresh mass plant-1, dry matter plant-1, leaf area, total chlorophyll content, photosynthetic rate (PN), nitrate reductase (NR) activity, yield parameters (ear number plant-1, length ear-1, spikelet number ear-1, grain number ear-1 and 1000 grain weight), ultimately resulting in improved grain yield as well as grain carbohydrate and protein content as compared to control as well as higher fertilizer doses. Thus wastewater application not only provided stable supply of water, but also saved fresh water and contributed to environmental security. Moreover, it reduced the use of chemical fertilizers without showing any adverse effect on the yield and quality of wheat. Physicochemical characteristics of wastewater along with microbiological and some heavy metals were analyzed, and most of them were within the permissible limits set by Food and Agriculture Organization (FAO).